Physiological role of FGF signaling in growth and remodeling of developing cardiovascular system - Krejci, E; Pesevski, Z; Nanka, O; Sedmera, D (Physiological research, 2016)
Fibroblast growth factor (FGF) signaling plays an important role during embryonic induction and patterning, as well as in modulating proliferative and hypertrophic growth in fetal and adult organs. Hemodynamically induced stretching is a powerful physiological stimulus for embryonic myocyte proliferation. The aim of this study was to assess the effect of FGF2 signaling on growth and vascularization of chick embryonic ventricular wall and its involvement in transmission of mechanical stretch-induced signaling to myocyte growth in vivo. Myocyte proliferation was significantly higher at the 48 h sampling interval in pressure-overloaded hearts. Neither Western blotting, nor immunohistochemistry performed on serial paraffin sections revealed any changes in the amount of myocardial FGF2 at that time point. ELISA showed a significant increase of FGF2 in the serum. Increased amount of FGF2 mRNA in the heart was confirmed by real time PCR. Blocking of FGF signaling by SU5402 led to decreased myocyte proliferation, hemorrhages in the areas of developing vasculature in epicardium and digit tips. FGF2 synthesis is increased in embryonic ventricular cardiomyocytes in response to increased stretch due to pressure overload. Inhibition of FGF signaling impacts also vasculogenesis, pointing to partial functional redundancy in paracrine control of cell proliferation in the developing heart.
Keywords: Chick Embryo; kardiomyocyty; Cell Proliferation; Pressure; Receptor, Fibroblast Growth Factor, Type 1; tlak; Animals; Myocytes, Cardiac; fibroblastový růstový faktor 2; zvířata; proliferace buněk; Heart; receptor fibroblastových růstových faktorů, typ 1; Fibroblast Growth Factor 2; srdce; kuřecí embryo